2009
DOI: 10.1212/01.wnl.0000341277.74885.ec
|View full text |Cite
|
Sign up to set email alerts
|

TP53 codon 72 polymorphism is associated with age at onset of glioblastoma

Abstract: Our data suggest that TP53 functional variation is particularly critical for oncogenesis of glioblastoma in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…The biological value of p53 Arg72Pro variant in cancer risk and progression is extremely controversial [6, 7, 31]. A possible explanation could be found in population genetics.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The biological value of p53 Arg72Pro variant in cancer risk and progression is extremely controversial [6, 7, 31]. A possible explanation could be found in population genetics.…”
Section: Discussionmentioning
confidence: 99%
“…The Arg72 isoform is more efficient in inducing apoptosis, while the Pro72 variant activates transcriptionally several p53-dependent genes involved in DNA-repair and cell-cycle arrest [5]. A possible association between TP53 codon 72 variants and cancer progression has been reported for several tumour types [615]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studying gastric cancer, Kim et al [31] found no correlation between any TP53 Pro72Arg allele and TP53 mutation; however, in their study, the TP53 mutational status was predicted by p53 protein immunopositivity, which might provide several false-negative cases [32,33]. On the other hand, El Hallani et al [34], studying glioblastomas, pointed to a relationship between the 72Pro allele and a TP53 somatic mutation. Indeed, this association seems to be dependent on the tumor tissue.…”
Section: Discussionmentioning
confidence: 99%
“…The correlation between genotype and age at cancer diagnosis has been studied for several cancer-related genes (Canedo et al 2008;El Hallani et al 2009). For survivin in particular, ¡31G > C polymorphism has been associated with age of onset of ovarian cancer (Han et al 2009).…”
Section: Discussionmentioning
confidence: 99%